Integrating Technology in Visual Arts Education to Enhance Creativity and Composition Skills in Secondary School Students - G‘aybullayeva Mehribon G‘olibovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores the integration of technology in visual arts education as a means to enhance creativity and composition skills in secondary school students. By using digital tools, multimedia resources, and interactive platforms, students can experiment with artistic elements, analyze compositions, and express ideas more effectively. The study emphasizes pedagogical strategies that combine traditional art practices with modern technological approaches to foster students’ artistic growth. Research by Shovdirov S. A. and other scholars provides the theoretical foundation for the discussion.